Retrieval of greenhouse gases from GOSAT and GOSAT-2 using the FOCAL algorithm - S. Noël; M. Reuter; M. Buchwitz; J. Borchardt; M. Hilker; O. Schneising; H. Bovensmann; J. P. Burrows; A. Di Noia; R. J. Parker; R. J. Parker; H. Suto; et al. (Atmospheric Measurement Techniques, 2022)
We show new results from an updated version of the Fast atmOspheric traCe gAs retrievaL (FOCAL) retrieval method applied to measurements of the Greenhouse gases Observing SATellite (GOSAT) and its successor GOSAT-2. FOCAL was originally developed for estimating the total column carbon dioxide mixing ratio (XCO2) from spectral measurements made by the Orbiting Carbon Observatory-2 (OCO-2). However, depending on the available spectral windows, FOCAL also successfully retrieves total column amounts for other atmospheric species and their uncertainties within one single retrieval. The main focus of the current paper is on methane (XCH4; full-physics and proxy product), water vapour (XH2O) and the relative ratio of semi-heavy water (HDO) to water vapour (δD). Due to the extended spectral range of GOSAT-2, it is also possible to derive information on carbon monoxide (XCO) and nitrous oxide (XN2O) for which we also show first results. We also present an update on XCO2 from both instruments.